CD4+ gain percentile curves for monitoring response to antiretroviral therapy in HIV-infected adults. (1st June 2015) - Yotebieng, Marcel; Maskew, Mhairi; Van Rie, Annelies
Abstract : Objectives: We constructed CD4 + cell count gain percentile distributions standardized by baseline CD4 + cell count and assessed the association between poor CD4 + cell count gain and subsequent death and virological failure on antiretroviral therapy (ART). Design: Secondary analysis of 10 years of clinical data from a cohort of adults initiated on ART at the Themba Lethu clinic in Johannesburg, South Africa. Methods: The generalized additive model for location, scale and shape was used to construct percentile curves for CD4 + cell count gain standardized by baseline CD4 + cell count in the first 28 months of ART. Cox proportional models were used to assess the association between lower percentiles (<50th) of CD4 + cell count gain, and subsequent death and virological failure. Results: Among 9640 nonpregnant adults 7406, with available CD4 + cell count results for CD4 + gain calculation at 4 months of ART, 843 (8.7%) died subsequently and 1101 (11.4%) experienced virologic failure, respectively. For CD4 + gains below the third percentile, the adjusted hazard ratios at different time points ranged between 2.72 and 5.73 for death, and between 1.48 and 6.93 for virologic failure. The CD4 + percentile curves revealed a gradient of increasing risk of subsequent death and virological failure, with lower CD4 + gain percentiles and increasing time on ART, and were more informative than the WHO criteria for immunological failure or current CD4 + cell count. Conclusion: Percentile curves of CD4 + cell count gain provide a simple tool for healthcare workers in low-resource settings to monitor response to ART with improved information regarding risk of death and virological failure compared to current WHO criteria for immunological failure. Abstract : Supplemental Digital Content is available in the text